Gereja Yang Elastis Sebagai Model Bergereja di Era Digital - Yudha Nugraha Manguju (Institut Agama Kristen Negeri Toraja, 2022)
Abstract: The church in the 21st century is undergoing such great development and change. This is due to the Industrial Era 4.0 which is marked by advances in digital technology and the COVID-19 pandemic which requires churches to rethink their ministry models in the digital space. The Church has entered a new era in the pattern of its ministry mediated by digital technology. This study aims to find models of churches that are emerging in the digital age by utilizing the idea of a liquid church in Pete Ward's thinking as a development of the new character of the church. The research method used is qualitative with a literature study and interview approach. This research shows that the face of the church in the digital era can be distinguished into four models, namely Analog Church, Digilog Church or Phygital Church, E-Church and Virtual Reality Church. The new characteristics offered in this paper are the